A Combined Experimental and Theoretical Study on the Formation of Ag Filaments on β‐Ag2MoO4 Induced by Electron Irradiation. (23rd January 2015) - Andrés, Juan; Ferrer, Mateus M.; Gracia, Lourdes; Beltran, Armando; Longo, Valeria M.; Cruvinel, Guilherme H.; Tranquilin, Ricardo L.; Longo, Elson
<x xml:space="preserve">Abstract</x> A combined experimental and theoretical study is presented to understand the novel observed nucleation and early evolution of Ag filaments on β‐Ag2MoO4 crystals, driven by an accelerated electron beam from an electronic microscope under high vacuum. The growth process, chemical composition, and the element distribution in these filaments are analyzed in depth at the nanoscale level using field‐emission scanning electron microscopy (FE‐SEM) and transmission electron microscopy (TEM) with energy‐dispersive spectroscopy (EDS) characterization. To complement experimental results, chemical stability, structural and electronic aspects have been studied systematically using first‐principles electronic structure theory within a quantum theory of atoms in molecules (QTAIM) framework. The Ag nucleation and formation on β‐Ag2MoO4 are a result of structural and electronic changes of the AgO4 tetrahedral cluster as a constituent building block of β‐Ag2MoO4, consistent with Ag metallic formation. The formation of Ag filament transforms the β‐Ag2MoO4 semiconductor from n‐ to p‐type concomitant with the appearance of Ag defects.